Procedimento de caracterização do ruído acústico de conversores estáticos aplicados em sistemas de iluminação - Viera, Eduardo Minuzzi (2024)
This paper presents the development of a methodology for the acoustic characterization of electronic systems, focusing on a 250 W driver for LED lamp operation, which consists of an LLC resonant converter and a power factor correction stage using a Boost converter. The developed methodology includes acoustic measurements for analyzing the noise emitted by the electronic converters, with frequency spectrum analysis and sound directivity evaluation, enabling a detailed understanding of the noise behavior. Comparisons of the measured acoustic noise are also performed as a function of variables such as load, voltage, and current at the system’s input and output. The measurements were based on the recommendations of Energy Star and ECMA-74. The methodology involved the use of an anechoic chamber and the development of a rotating table. The measurements revealed that the acoustic noise from the LLC converter exhibited a higher amplitude around 11 kHz, with variations in sound pressure levels depending on the operational mode and load configuration. The PFC converter, on the other hand, showed higher acoustic noise amplitude at 120 Hz, while at frequencies above 500 Hz, the noise generated by the converter was close to the background noise level. Finally, it is concluded that this work contributes to the development of a methodology for measuring acoustic noise in electronic systems. The research also broadens the understanding of the interactions between acoustic noise and the operating conditions of electronic converters, emphasizing the importance of detailed characterization methods for practical applications.